FREQUENCY OF NEONATAL THYROID DISORDERS IN A TERTIARY CARE HOSPITAL IN KARACHI - Erum Salim; Sumera Shaikh; Najia Tabassum Mahfooz; Adnan Zubairi; Shanawer Ali Khawaja; Areebah Asim (ziauddin University, 2019)
Background: Thyroid hormone is necessary for metabolism, growth and brain development. Thyroid-stimulating hormone (TSH) secreted by anterior pituitary gland acts on thyroid to release thyroid hormones T3 and T4. Insufficient production of thyroid hormone at birth is known as congenital hypothyroidism (CH). CH leads to intellectual impairment, if not identified. Neonatal hyperthyroidism is relatively uncommon The objective of this study is to determine the frequency of thyroid disorders in neonates born in a tertiary care hospital. Methods: This is retrospective cross-sectional, observational study carried out at the tertiary care hospital Karachi, from October 2017 to May 2018. Screening for thyroid disorders is mandatory for newborns born in our hospital. Only data of neonates with thyroid stimulating hormone (TSH) performed was included for this study. TSH levels of these patients were determined by immunoassay on Vitros Enhanced Chemiluminescence technique. Results: In this study, 383 neonates were included, who were born in Ziauddin Hospital Clifton and /or were presented in Ziauddin hospital laboratory for TSH testing. The average age of neonates was 4.11+/-4.14 days and average TSH levels were 4.58+/-4.32 µIU/ ml. They were divided into two groups: Group# I from birth to 4days of life, 305 neonates were included in which 278(91.1%) were euthyroid and 27(8.9%) were hyperthyroid. None of neonates found hypothyroid in this age group. Group# II from 5 days to 1 month of life, only 78 neonates were included, 55(70.5%) were euthyroid, 18(23.1%) were hypothyroid and 5(6.4%) were hyperthyroid. Conclusion: Neonatal screening for thyroid disorders is very beneficial for patients as well as their families and also gives information regarding these disorder's epidemiology, pathophysiology, diagnosis and treatment in infantile period.